Fallhendelser hos eldre i hjemmetjenesten i en norsk kommune- omfang og omstendigheter - Solbakken, Rita; Bondas, Terese (Nordisk tidsskrift for helseforskning, 2015)
Fall events in elder recipients of home care services in a Norwegian municipality- incidence and circumstances Falls in institutional care are adverse events that have been well documented. Falls among elderly in home care services have not previously been studied in Norway. The aim of this study was to register the incidence and circumstances surrounding falls occurring in home-care services for elderly persons in a medium-sized Norwegian municipality. Descriptive statistics was applied in a three-month follow up study. Totally 440 homebound elderly aged 65 years or more and receiving home care services or safety alarm were included in this study. In total 101 falls, represented by 72 persons were documented. Sixty six percent reported no injury related to the fall, but 34% had injuries, ranging from bruises to fractures and hospitalization. In 24 % the circumstances were unknown, for the rest there was no particular cause documented. The findings will be used to study the development of care and prevention of falls with elder persons in home care services.